Moving Forward the Defense Line and Wasting No Time: The Era of Active Prevention and Control of Hypertension in China Has Come - LOU Ying; CAI Jun (Xiehe Yixue Zazhi, 2024)
To comprehensively improve the level of standardized screening, diagnosis and treatment of hypertension, the Clinical practice guidelines for the management of hypertension in China has been jointly initiated by Chinese Society of Cardiology, Chinese Medical Association, Hypertension Committee of Cross-Straits Medicine Exchange Association, Cardiovascular Disease Prevention and Rehabilitation Committee, and Chinese Association of Rehabilitation Medicine. This guideline addresses several important clinical problems in the field of screening, diagnosis evaluation and treatment of hypertension, fully assesses the latest high-quality clinical research evidences available, and gives clear recommendations. It also advocates the new concepts and perspectives, such as moving forward the diagnosis and treatment of hypertension, promoting the target of blood pressure reduction, simplifying the risk stratification of cardiovascular diseases, and paying attention to the screening of secondary hypertension, which will help promote the prevention and treatment of hypertension in China.